2018
DOI: 10.1007/s12020-018-1707-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative-pressure wound therapy for management of chronic neuropathic noninfected diabetic foot ulcerations – short-term efficacy and long-term outcomes

Abstract: PurposeNegative pressure wound therapy (NPWT) is an adjunct method used in the treatment of diabetic foot ulceration (DFU). Real world data on its effectiveness and safety is scarce. In this prospective observational study, we assessed the short-term efficacy, safety, and long-term outcomes of NPWT in patients with type 2 diabetes (T2DM) and neuropathic, noninfected DFUs.MethodsBased on wound characteristics, mainly area (>1 vs. ≤1 cm2), 75 patients with DFUs treated in an outpatient clinic were assigned to NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…Again, a greater proportion of ulcers treated with NPWT achieved healing than in the comparator treatment group—46.3% vs 32.8% at 20 weeks. Our results based on the meta‐analysis of this American paper and about a dozen of other nonrandomized studies, including our local Krakow observational data, showed an advantage of NPWT therapy in one important outcome—major amputation rate.…”
Section: Negative Pressure Wound Therapy Clinical Human Studies and Imentioning
confidence: 58%
“…Again, a greater proportion of ulcers treated with NPWT achieved healing than in the comparator treatment group—46.3% vs 32.8% at 20 weeks. Our results based on the meta‐analysis of this American paper and about a dozen of other nonrandomized studies, including our local Krakow observational data, showed an advantage of NPWT therapy in one important outcome—major amputation rate.…”
Section: Negative Pressure Wound Therapy Clinical Human Studies and Imentioning
confidence: 58%
“…For a better use of the surgical management arsenal, in our departament was imagined and conceived a therapeutic-prognostic index to help the surgeon establish an adequate procedure (18,19). As an alternative to surgical management for chronic neuropathic nonifected diabetic ulcers, negative pressure wound therapy did not prove its effectiveness over standard therapy, hight rates of recurrence being reported (20). In diabetic foot ulcers patients, the risk of limb amputation depends on severity of infection at the initial presentation, previous history of lower extremity amputation, peripheral arterial disease and presence of any walking disability.…”
Section: Discussionmentioning
confidence: 99%
“…In total four RCTs, three cohort studies and one case control were found comparing the use of NPWT with standard of care, all of which were at high risk of bias …”
Section: Negative Pressure Wound Therapy or Compressionmentioning
confidence: 99%
“…The findings from two other cohort‐controlled studies, while indicating apparent benefit, could not be easily interpreted due to unclear statistical analysis, and both were considered at high risk of bias. A recent prospective observational cohort did not report a difference in ulcer healing outcomes at 1 year, but allocation to NPWT if ulcer area was more than 1 cm 2 or to a comparator if less than 1 cm 2 would have introduced significant bias. Moreover, adequate description of the comparator was not provided.…”
Section: Negative Pressure Wound Therapy or Compressionmentioning
confidence: 99%
See 1 more Smart Citation